The Influence of the Environment in the Public Policies of Spatial Planning - Solano Coto, Erick (2016)
During the twentieth century in Costa Rica, spatial planning and environmental policies, as well as their implementation tools, proved they have been inefficient or insufficient to avoid, or at least, to reduce, the negative impacts produced over the environment by the multiple activities developed by humans. However, during the past two decades -mainly, since article 50 of the Constitution was modified in 1994, enabling the right to enjoy an ecologically balanced and wholesome environment- we can find legislative, administrative and communitarian efforts, looking forward to an adequate harmony amid human activities, environmental protection and cities organized development. Without a doubt, the environmental factor has acquired an increasing relevance in the country during the last twenty years. This has been materialized by the enactment of laws and bylaws, trying to achieve not only environmental protection, but also support - direct or indirectly - the absence of urbanistic laws and regulations.To determine with accurate precision, from a legal perspective, the incidence of the environmental factor in spatial and urban planning, through the mentioned laws and bylaws, the public policies and their implementation tools, is the purpose of this paper; and also, to offer an analysis about the administrative and judicial decisions, that may allow the identification of the results - positive or not- over the Public Administrations and the citizens. The later, with the aim to recognize their effects, and define towards the future, which bearings may and must be improved. This in order to conquer a social economic cohesion and a plain sustainable development that will positively affect citizens’ quality of life.